High Rate of Ceramic Sandwich Liner Fracture - Lopes, Ronny (Springer-Verlag, 2012)
BACKGROUND: Ceramic bearing surfaces for THA were introduced to reduce the risk of wear. However, owing to liner fracture in some of the early series and presumption that the fractures were the result of the modulus mismatch of the implant and the bone, a ceramic sandwich liner with lower structural rigidity was introduced. Fractures of these devices also were reported subsequently, although the incidence is unclear and it is unknown whether there are any risk factors associated with the fractures. QUESTIONS/PURPOSES: We therefore determined the incidence of these fractures. METHODS: We retrospectively reviewed 298 active patients in whom we implanted 353 ceramic-polyethylene sandwich liner acetabular components between November 1999 and February 2008. The mean age of the patients was 53.6 years (range, 17–84 years). The minimum followup was 6 months (mean, 41 months; range, 6–106 months). All patients were assessed clinically and radiographically. RESULTS: Seven of the 353 (2%) ceramic sandwich liners fractured at a mean of 4.3 years (range, 1.3–7.6 years) after surgery without trauma. Neither patient-related factors nor radiographic position of the implants were risk factors for fracture. CONCLUSIONS: Owing to the high rate of fractures of the sandwich ceramic polyethylene liners in our patients, we have discontinued use of this device. LEVEL OF EVIDENCE: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.